Chorology, flight curves and diel activity of oak-living clear-wing moths in Extremadura, SW Spain (Lepidoptera: Sesiidae) - Luis M. Torres-Vila; Adrián J. Montero-Calvo; F. Javier Mendiola-Díaz; Rafael López-Calvo; Álvaro Sánchez-González; Francisco Ponce-Escudero; Félix Fernández-Moreno; Zdeněk Laštůvka (Forest Systems)
Aim of study: To acquire data on the chorology, phenology and diel activity of oak-living clear-wing moths, given the increased phytosanitary impact of some species.